Clinical effect of the therapeutic apparatus for music therapy based on Traditional Chinese Medicine syndrome differentiation in the treatment of functional abdominal distension (中医辨证移情音乐胃肠治疗仪改善功能性腹胀临床疗效观察) - YANG Yanming (杨艳明); LIU Shu (刘姝); HUANG Yanping (黄砚萍); LIU Fenling (刘粉玲); LONG Yang (龙洋); LI Xiang (李想); LUO Huimin (罗慧敏); ZHONG Yuan (钟远) (中西医结合护理)
Objective To observe the effect of using the therapeutic apparatus for music therapy based on Traditional Chinese Medicine (TCM)syndrome differentiation in the treatment of functional abdominal distension. Methods Totally 60 patients with functional abdominal distension were randomly divided into the control group and the intervention group, with 30 cases in each group. All patients received a routine treatment and nursing (7 days per course, two courses), and the music therapy based on TCM syndrome differentiation by using a therapeutic apparatus was performed in the intervention group. The Gastrointestinal Symptom Assessment score and overall effective rate were compared between two groups. Results The Gastrointestinal Symptom Assessment score decreased in both two group after two courses of treatment, and the Gastrointestinal Symptom Assessment score in the intervention group was lower than that in the control group(P＜0. 01). The overall effective rate was 93. 33%(28/30) in the intervention group, which was significant higher than 73. 33%(22/30) in the control group(P＜0. 01). No serious adverse reaction was reported in either group. Conclusion The therapeutic apparatus for music therapy based on TCM syndrome differentiation is safe and effective in the treatment of functional abdominal distension. (目的 观察运用中医辨证移情音乐胃肠治疗仪改善功能性腹胀的效果。方法 将符合纳入标准的60例功能性腹胀患者随机分为两组, 各30例。对照组接受常规治疗和护理, 干预组在常规治疗的基础上采用中医辨证移情音乐胃肠治疗仪。两组均以7 d为1个疗程, 共2个疗程。记录与评价患者腹胀症状, 对比两组干预效果。结果 干预后, 两组胃肠症状评分均较干预前下降, 且干预组胃肠症状评分低于对照组, 差异有统计学意义(P＜0. 01)。干预组总有效率93. 33%(28/30), 高于对照组的73. 33%(22/30), 差异有统计学意义(P＜0. 05)。两组均无严重不良反应。结论 中医辨证移情音乐胃肠治疗仪改善功能性腹胀具有较好的疗效, 且安全可行。)